Use of blue-greenish yellow fluorescence test on feeds and its association with aflatoxin M1contamination in bulk tank milk - Wantanwa Mongkon (2018)
The objectives of this study were to use the blue-greenish yellow fluorescence (BY) test for aflatoxin M1 (AFM1) contamination in bulk milk and to examine the association between AFM1 contamination and environmental and feed management factors. The study was conducted March to May of 2011 with samples from 82 small holder dairy farms belonging to a single dairy cooperative in Chiang Mai province, Thailand. On the day of milk sample collection, samples of all feed used for milking cows and data on feed characteristics, feed management, and environmental factors also were collected at each farm. High-performance liquid chromatography was used to determine AFM1 concentrations in milk samples, and samples with AFM1 concentrations above the limit of detection were considered AFM1 contaminated. Fisher's exact tests were used to determine the association between AFM1 contamination in milk and farm management factors, feed management factors, and fungal contamination in feeds (as determined with the BY test). A multilevel logistic regression model was used to create the final model of factors associated with AFM1 contamination in milk. Feeds with fungal contamination (as determined by the BY test), high levels of cracked particles of commercial concentrate pellets, sunlight in the feed storage room, storage of commercial concentrates on the farm for more than 1 month, and more than 5% difference in relative humidity between the feed storage room and the barn holding lactating cows were associated with AFM1 contamination in milk. The BY test was useful for screening cattle feed for fungal contamination, and the results of this test in conjunction with other factors can be used to monitor and prevent AFM1 contamination in milk on small holder dairy farms. © International Association for Food Protection.